PENERAPAN MODEL PROBLEM BASED LEARNING SECARA DARING DALAM MENINGKATKAN HASIL BELAJAR FISIKA MATERI ELASTISITAS DAN HUKUM HOOKE PADA SISWA KELAS XI SMA NEGERI 1 TONDANO - Sumita Ginoga; Patricia Mardiana Silangen; Jeferso Polii (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to improve physics learning outcomes by using the Problem Based Learning model. The research method used is a class action research method using two cycles. The learning device used is, lesson plan. The KKM determined at school is 75. In the first cycle of the material on Elasticity and Hooke's Law the number of students who completed the KKM was 10 people and in the second cycle the number of students who completed there were 26 people. So the results of the study show that by giving the action of applying the Problem Based Learning model, the average class percentage increases when students complete their studies. It was concluded that there was a result of learning Physics on Elasticity and Hooke's Law material in class XI IPA 4 SMA Negeri 1 Tondano.